MAJAS LITOTES DALAM LIRIK LAGU ALBUM ETHIOPIA KARYA IWAN FALS (KAJIAN STRUKTURAL) - Muhammad Mun’im; Afif Rofii; Uli Wahyuni (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research was motivated by people's ignorance of the litotes figure of speech. One of the literary works that uses the litotes figure of speech is a song. This research aims to analyze the function of the litotes figure of speech in the lyrics of the song Album of Ethiopia by Iwan Fals. The analysis of this research will answer the research questions and research objectives, namely, to describe the function of the litotes figure of speech which includes the function of making a more subtle statement, increasing the attractiveness of the message, explaining a certain meaning in language that is easy to understand, producing an imaginative effect for the interlocutor, and creates a shock effect. This research will illustrate how litotes function as strength in songs. This research method is a qualitative descriptive method. With this research method, researchers can describe the results of research on how the function of the litotes figure of speech is to make a more subtle statement, increase the attractiveness of the message, explain a certain meaning in language that is easy to understand, produce an imaginative effect for the interlocutor, and the function of creating a surprise effect in the lyrics. song. The results of this research can be explained that the function of the litotes figure of speech in the lyrics of the song Album of Ethiopia by Iwan Fals tends to be that the function of the litotes figure of speech increases the appeal of the message. This can be seen in the quotes found in the function of increasing the attractiveness of the message, namely 24 quotes. Apart from that, there are 14 quotations for making polite and subtle statements, 17 quotations for explaining a certain meaning in language that is easy to understand, 22 quotations for producing an imaginative effect for the interlocutor, and 2 quotations for the function of creating a surprise effect. In other words, the total number of litotes figure of speech functions found in this album is 79 quotations.